Respon Pertumbuhan dan Hasil Tanaman Jagung Manis (Zae Mays Saccharata Sturt.) Terhadap Pemberian Dua Jenis Pupuk Organik - Mokhamad Sholeh; Antar Sofyan; Akhmad Rizali (Agroekotek View, 2021)
Sweet corn or Zea mays Saccharata Sturt. is a horticultural plant that is well known by the public for its delicious taste and distinctive aroma. Excessive use of pesticide fertilizers, which are inorganic materials, can reduce the production of sweet corn as a result of decreasing the quality of agricultural land. Alternative use of organic fertilizers as a substitute for inorganic fertilizers is more effective in increasing the production of sweet corn because organic fertilizers contain micro nutrients in sufficient quantities and are able to improve the biological, physical, and also chemical properties of the soil. Organic fertilizers have more advantages than chemical or inorganic fertilizers, including that organic fertilizers can improve soil properties and keep the soil from degrading or degradation. This study aims to determine the response to growth and the type of organic fertilizer that was best for the growth and yield of sweet corn (Zae Mays Saccharata Sturt.). This study used a Randomized Block Design (RBD) which consisted of 1 factor and 4 levels of treatment, including the first treatment: NPK fertilizer (P0); second treatment: NPK fertilizer plus organic fertilizer made from tricoderma sp. (P1); third treatment: NPK fertilizer plus organic fertilizer made from mixed biodex (P2); and fourth treatment: NPK fertilizer plus organic fertilizer made from tricoderma sp. and biodex (P3). The results showed that there was effectiveness and response to the application of several types of NPK fertilizers plus organic fertilizers made from tricoderma sp. (P1), NPK fertilizer plus organic fertilizer made from mixed biodex (P2), and NPK fertilizer plus organic fertilizer made from tricoderma sp. and biodex (P3) which significantly affected plant height, leaf number, leaf width, ear number, and wet weight compared to control treatment on the growth and yield of Sweet Corn (Zae Mays Saccharata Sturt.). Type of NPK fertilizer plus organic fertilizer made from trichoderma sp. and Biodex (P3) is the best type of organic fertilizer for the growth and yield of sweet corn.